2003
DOI: 10.1246/cl.2003.482
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TTP Donor Containing a PROXYL Radical for Magnetic Molecular Conductors

Abstract: A TTP donor containing a stable PROXYL radical was synthesized to develop conducting-magnetic bifunctional materials and its structure and physical properties were investigated. Furthermore its cation radical salts were prepared and revealed their conducting and magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Therefore many researchers have introduced organic radicals in organic conducting salts. For example, charge-transfer (CT) salts of free radical substituted organochalcogen donors [7][8][9][10][11][12][13][14][15][16], CT complexes of free radicals and acceptors [17][18], CT salts of free radical substituted cations and acceptors [19][20][21][22][23], have been reported.…”
mentioning
confidence: 99%
“…Therefore many researchers have introduced organic radicals in organic conducting salts. For example, charge-transfer (CT) salts of free radical substituted organochalcogen donors [7][8][9][10][11][12][13][14][15][16], CT complexes of free radicals and acceptors [17][18], CT salts of free radical substituted cations and acceptors [19][20][21][22][23], have been reported.…”
mentioning
confidence: 99%
“…After the column-chromatographic separation of the resultant mixture, donor molecule 1 having a vinylene spacer was obtained as air-stable orange microcrystals in 53% yield. radical salts using bis-fused TTF (TTP = 2,5-bis(1,3-dithiol-2-ylidene)-1,3,4,6-tetrathiapentalene) donors and a PROXYL radical [14][15][16]. Furthermore, we have developed new TTF and TTP donors containing a 2,2,5,5-tetramethylpyrrolin-1-yloxyl radical [17] because this radical part has an unsaturated 3-pyrroline ring with a C=C bond and smaller steric hindrance in comparison to the PROXYL radical having a saturated 3-pyrrolidine ring.…”
Section: Synthesis Of Donormentioning
confidence: 99%
“…On the other hand, the studies on molecular conductors using donor molecules substituted with stable organic radicals such as 2,2,6,6-tetramethylpiperidin-1-yloxyl (TEMPO) and nitronyl nitroxide radicals have been performed by several research groups [6][7][8][9] because cation radical salts of such stable radical-containing donors are expected to have strong intramolecular magnetic interactions between their π-cation radical spins and stable radicals and to show outstanding responses to the application of external magnetic fields [10]. Among them, we have also reported several tetrathiafulvalene (TTF)-based donor molecules containing stable organic radical parts such as TEMPO and 2,2,5,5-tetramethylpyrrolidin-1-yloxy (PROXYL) radicals [11][12][13], and discovered highly conducting cation radical salts using bis-fused TTF (TTP = 2,5-bis(1,3-dithiol-2-ylidene)-1,3,4,6-tetrathiapentalene) donors and a PROXYL radical [14][15][16]. Furthermore, we have developed new TTF and TTP donors containing a 2,2,5,5-tetramethylpyrrolin-1-yloxyl radical [17] because this radical part has an unsaturated 3-pyrroline ring with a C=C bond and smaller steric hindrance in comparison to the PROXYL radical having a saturated 3-pyrrolidine ring.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The black crystals of (TTP-PROXYL)MCl 4 (M ¼ Fe and Ga) were prepared electrochemically. The X-ray crystal structure analyses revealed that the FeCl 4 salt was isostructural to the GaCl 4 salt and belonged to the triclinic system.…”
Section: K Emu Molmentioning
confidence: 99%